2008
DOI: 10.1158/0008-5472.can-08-2309
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Hypertension, Preeclampsia, and Risk of Testicular Cancer

Abstract: Altered levels of pregnancy hormones have been suggested to initiate testicular cancer prenatally in the male fetus. The placenta is the main source of pregnancy hormones, and pregnancy hypertension and preeclampsia are associated with placental malfunction, including altered levels of hormones such as estrogen and human chorionic gonadotropin. We therefore evaluated fetal exposure to pregnancy hypertension and preeclampsia in relation to risk of testicular cancer in adolescent and adult life. We identified 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Six studies were included in the meta-analysis (Pettersson et al , 2008; Sonke et al , 2007; Coupland et al , 2004; Weir et al , 2000; Moller et al , 1997; Depue et al , 1983). One study (Mori et al , 1988; Mori et al , 1990) involved a very small number of cases (37) and controls (37) and provided two categories of BMI (high [>25] and moderate [<25]) and therefore was not included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies were included in the meta-analysis (Pettersson et al , 2008; Sonke et al , 2007; Coupland et al , 2004; Weir et al , 2000; Moller et al , 1997; Depue et al , 1983). One study (Mori et al , 1988; Mori et al , 1990) involved a very small number of cases (37) and controls (37) and provided two categories of BMI (high [>25] and moderate [<25]) and therefore was not included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies contributed to the analysis (Pettersson et al , 2008; Sonke et al , 2007; Coupland et al , 2004; Weir et al , 2000; Mori et al , 1990; Depue et al , 1983). The study by Moller et al (Moller et al , 1996) could not be included in this analysis because it reported weight and not BMI.…”
Section: Resultsmentioning
confidence: 99%
“…The placenta is the main source of hormones associated with pregnancy and is typically the tissue that is influenced in PE. Therefore, the PE is characterized by a disturbance in the fundamental balance between steroids and β‐hCG hormones in a manner that reflects abnormal placentation, placental dysfunction and abnormal placental secretory function . This includes elevated β‐hCG production by hyperplastic cytotrophoblastic cells in PE and lowers E2 and excess of PRG values in PE women.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a delayed androgen activity may be associated with a reduced lifetime risk for prostate [42] and testicular cancer. [43,44]…”
Section: Discussionmentioning
confidence: 99%